2008
DOI: 10.2106/jbjs.g.00755
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Total Hip Arthroplasty with Alumina Bearings in Patients Younger Than Fifty with Femoral Head Osteonecrosis

Abstract: After a minimum of six years of follow-up, this cementless total hip arthroplasty with contemporary alumina bearings was found to be a promising procedure for young, active patients with osteonecrosis of the femoral head. However, we remain concerned about the long-term implications of the noise that was reported in these hips.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 23 publications
5
55
0
1
Order By: Relevance
“…According to a 10-year followup study by Kim et al [21], no osteolysis was observed in 93 hips of patients operated on when the patients were younger than 45 years, and this result was supported by CT scans. Similar results were reported by Baek and Kim [1]. In our study, no appreciable osteolysis was observed by plain radiography (Table 3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to a 10-year followup study by Kim et al [21], no osteolysis was observed in 93 hips of patients operated on when the patients were younger than 45 years, and this result was supported by CT scans. Similar results were reported by Baek and Kim [1]. In our study, no appreciable osteolysis was observed by plain radiography (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…Several reports describe alumina-on-alumina bearings used in THAs in young patients [1,3,19,30], and report survivorship ranging from 91% to 99% at 7 to 11 years [10,11,21,24]. We previously reported 5-year followup results of patients younger than 40 years [38], and 10-year followup results in a series of 100 patients [24].…”
Section: Introductionmentioning
confidence: 99%
“…The results of ceramic-on-ceramic bearings in patients who were older than 40 years have been reported [2,3,16,29,30], but few [6,15,23] have focused on the long-term results of ceramic-on-ceramic implants in patients younger than 20 years. In this series, we found the survivorship of ceramic-on-ceramic implants in adolescent patients was encouraging, averaging 90.3% at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Five patients reported some transient noise (one squeak), but none underwent revision surgery for this problem. The proportion of patients reporting squeaking varies considerably, ranging from less than 1% to 20% [2,24]. In a prospective observational study of 1486 ceramic-on-ceramic THAs, 95 hips (6%) had squeaking develop [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation